2021
DOI: 10.1021/acsanm.1c03141
|View full text |Cite
|
Sign up to set email alerts
|

11-Mercaptoundecanoic Acid-Functionalized Carbon Dots As a Ratiometric Optical Probe for Doxorubicin Detection

Abstract: A ratiometric optical dual-mode probe was first designed for the detection of doxorubicin (DOX) based on 11-mercaptoundecanoic acid-functionalized carbon dots (MUA-CDs). The carbon dots (CDs) were synthesized via hydrothermal carbonization of m-phenylenediamine and p-aminobenzoic acid, and then it was reacted with 11-mercaptoundecanoic acid by the amide reaction to obtain the MUA-CDs. The as-synthesized MUA-CDs have a high fluorescence quantum yield (59.4%) with bright green emission. Based on a specific elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 50 publications
(89 reference statements)
2
13
0
Order By: Relevance
“…S6 †) can reach over 85% upon the addition of the NCs at a concentration of 100 μg mL −1 . This result is close to that of MUA-functionalized carbon dots at the same concentration reported by Zhang et al, 37 and much higher than that of glutathione-capped CdTe/ZnS NCs at a concentration of 10 μg mL −1 reported by Song et al 14 This suggests the low cytotoxicity of the AgGaSe 2 / ZnSe NCs, which can be attributed to the toxic element free in AgGaSe 2 as well as the effective reduction of cation leakage by the ZnSe shell. Subsequently, the water-soluble AgGaSe 2 /ZnSe NCs (100 μg mL −1 ) were used for intracellular imaging through incubation with HeLa cells directly.…”
Section: Dalton Transactions Papersupporting
confidence: 92%
“…S6 †) can reach over 85% upon the addition of the NCs at a concentration of 100 μg mL −1 . This result is close to that of MUA-functionalized carbon dots at the same concentration reported by Zhang et al, 37 and much higher than that of glutathione-capped CdTe/ZnS NCs at a concentration of 10 μg mL −1 reported by Song et al 14 This suggests the low cytotoxicity of the AgGaSe 2 / ZnSe NCs, which can be attributed to the toxic element free in AgGaSe 2 as well as the effective reduction of cation leakage by the ZnSe shell. Subsequently, the water-soluble AgGaSe 2 /ZnSe NCs (100 μg mL −1 ) were used for intracellular imaging through incubation with HeLa cells directly.…”
Section: Dalton Transactions Papersupporting
confidence: 92%
“…A high-resolution XPS spectrum was analyzed to reveal the forms of the four elements. As depicted in Figure 1e− 42 The deconvoluted Cl 2p spectrum at 198 and 199.5 eV showed the existence of Cl 2p 3/2 and Cl 2p 1/2 , respectively. 43 A systematic study was conducted to gain insight into the optical properties.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…The peak of N 1s was deconvoluted into pyridine N (398.8 eV), amino N (399.7 eV), and pyrrole N (400.5 eV) . CO bonds at 531.4 eV and C–O/C–O–C bonds at 532.6 eV were detected in the O 1s spectrum . The deconvoluted Cl 2p spectrum at 198 and 199.5 eV showed the existence of Cl 2p 3/2 and Cl 2p 1/2 , respectively …”
Section: Resultsmentioning
confidence: 98%
“…Recently, fluorescent carbon dots (CDs) have received widespread attention due to their advantages of cost-effective preparation, high water solubility, biocompatibility, and low toxicity. In addition to a wide range of applications like bioimaging, nanomedicines, drug delivery, etc., CDs-based probes have also been used for the detection of ions, molecular substances, etc. However, limited investigations have been carried out toward the detection of DOX using CDs-based fluorimetric and colorimetric methods. Hao et al reported polyethylimine-functionalized CDs for the detection of DOX by an inner filter effect (IFE) . Later, nitrogen- and phosphorus-codoped CDs were employed for the sensing of DOX .…”
Section: Introductionmentioning
confidence: 99%
“…The ratiometric fluorescence detection system has the advantage of multiple fluorescent color changes for easy visualization. Because of its convenience and visual detection, fluorescence/colorimetry dual-mode detection of DOX was developed by Dong and co-workers utilizing 11-mercaptoundecanoic acid-functionalized CDs …”
Section: Introductionmentioning
confidence: 99%